The Effect of C:N Ratio Level on Water Quality Parameters and Growth of Whiteleg Shrimp (Litopenaeus vannamei) with a Non-Water Exchange Cultivation System Using Molasses as an Organic Carbon Source - Panjaitan, Pohan (EDUCTUM: Journal Research, 2025)
One of the main obstacles to development of intensive aquaculture is the accumulation of toxic inorganic nitrogen which should be kept very low by frequent water exchange or recycling of the water through a biofilter. This study describes another method of removing inorganic nitrogen using heterotrophic bacteria population of which was augmented by the addition of a carbonaceous substance, molasses, to increase the feed C:N ratio under laboratory condition. The principal aim of laboratory study was to establish correlation C:N ratio level with levels of ammonia, nitrite, dissolved oxygen, pH and shrimp growth in Penaeus monodon shrimp culture with Zero Water Exchange Model (ZWEM) using molasses as carbon resource. It was found that addition of molasses to shrimp farming with ZWEM had role in removing ammonia and nitrite. Also, application of molasses to laboratory tanks increased the growth and percentage weight gain of shrimps and increased the population of heterotrophic bacteria.